Effect of flavour manipulation on ENDS (JUUL) users' experiences, puffing behaviour and nicotine exposure among US college students. Issue 4 (23rd May 2020) - Vargas-Rivera, Mayra; Ebrahimi Kalan, Mohammad; Ward-Peterson, Melissa; Osibogun, Olatokunbo; Li, Wei; Brown, David; Eissenberg, Thomas; Maziak, Wasim
Abstract : Significance: Electronic nicotine delivery system (ENDS) use has continued to increase exponentially among young people in the USA, with unique flavours being one of the most cited reasons for use. Yet, controlled studies examining the effects of restricting flavour are lacking. This study evaluates the impact of ENDS flavour manipulation on user's puffing behaviour, subjective experience, harm perception and nicotine exposure among college-aged ENDS users. Methods: JUUL users (n=30, age 18 to 24 years) attended two 60 min ad libitum ENDS use sessions (JUUL preferred flavour vs JUUL classic tobacco flavour) in a cross-over design. Puff topography and plasma nicotine concentration were measured, and participants completed subjective experience questionnaires. Results: Increases were observed on measures of satisfaction, taste, enjoyment, urges to vape/smoke, pleasure, product appeal and increased concentration following using the preferred flavour pod (p values <0.05). Compared with preferred flavour, participants in the tobacco flavour were less motivated to use it in the future (70.9 vs 19.1 scores, p<0.001), even if it was the only product on the market (75.8 vs 30.7 scores, p<0.001). While nicotine levels significantly increased in both conditions from pre to post session (p values <0.001), no significant differences were observed in nicotine boost levels or on puff topography parameters when comparing both flavour conditions. Conclusions: This pilot study provides evidence that ENDS flavours have a substantial effect in enhancing young current ENDS users' experiences, product appeal and motivation to use the product in the future. It highlights that limiting flavours could play a potential role when designing strategic policies to reduce the appeal of ENDS use among young people.